Traditional knowledge of animal-derived medicines used by Gelao community in Northern Guizhou, China - Xiaoqi Liu; Shuo Li; Yi Feng; Xingxing Chen; Yuhan Ma; Hai Xiao; Yongxia Zhao; Sha Liu; Guishen Zheng; Xiujuan Yang; Faming Wu; Jian Xie (BMC, 2024)
Abstract Introduction This study aims to document and preserve the traditional medicinal knowledge of the Gelao community in Northern Guizhou, China, providing valuable insights for modern pharmacological research and the development of these traditional remedies. Methods Our methodology encompassed a blend of literature review, community interviews, and participatory observation to delve into the traditional knowledge of animal-derived medicines among the Gelao community. We employed quantitative ethnological and ecological assessment techniques to evaluate the significance of these practices. Informed consent was secured before conducting interviews, with a focus on ascertaining the types of medicines familiar to the informants, including their local names, sources, methods of preparation, application techniques, diseases treated, frequency of use, and safety considerations. Results Our research cataloged 55 varieties of animal-derived medicines utilized by the Gelao people. Out of these, 34 originate from wild animals, mainly encompassing small insects, reptiles, and aquatic species; the remaining 21 are derived from domesticated animals, largely involving their tissues, organs, and various physiological or pathological by-products. These medicines are primarily applied in treating pediatric ailments (13 types), internal disorders (11 types), gynecological issues (3 types), dermatological problems (7 types), ENT conditions (3 types), trauma-related injuries (5 types), joint and bone ailments (5 types), infections (2 types), dental issues (2 types), and urolithiasis (1 type), with three types being used for other miscellaneous conditions. Commonly utilized medicines, such as honey, Blaps beetle, chicken gallstones, and snake-based products, are preferred for their availability, edibility, and safety within the Gelao communities. Conclusion The Gelao community's traditional medicines represent a rich diversity of animal sources, showcasing extensive expertise and knowledge in their processing and clinical applications. This wealth of traditional knowledge offers novel perspectives for the contemporary pharmacological study and development of these remedies. Additionally, our research plays a crucial role in aiding the preservation and continuation of this invaluable cultural heritage.